Principal Management in Improving Teacher Professionalism in Elementary School - Junaedi, Agi; Asy’ari, Hasyim; Maknuun, Lu’lu’ Il (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This research uses a type of qualitative research with a qualitative descriptive approach. The object of this research was carried out at SD Negeri Paripurna. Data collection techniques using Observation, Interview, and Documentation. Sources of data in this study included school principals, Deputy Head of Curriculum Affairs, PAI teachers, and class teachers at SD Negeri Paripurna. The analysis techniques used in this study are data collection, data reduction, data presentation, and conclusion. The triangulation used to test the validity of the data is technique and source triangulation. The results showed that (1) the management of the principal at SD Negeri Paripurna, Sumedang Regency, consisted of planning, organizing, implementing, and supervising. The planning carried out by the principal includes the school's vision and mission, and work programs to improve teacher professionalism. Implementation, the program carried out by the school principal, namely the implementation of the management strategy